Public space without architectural barriers as friendly and accessible for people with disabilities - Rawski, Kamil (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2017)
Accessible public space for people with disabilities is the space where there are no barriers that prevent them from normal functioning in a given place. In this paper, there was collected a number of examples of most common barriers and design guidelines needed to plan or transform space into the accessible one. There was also described type of barriers and factors that affect on the accessibility of the public space.